MECHANISMS AND METHODS FOR INCREASING WOMEN'S EMPLOYMENT (Ustozlar uchun, 2025)
Ensuring women's employment and reducing unemployment in the country is a complex socio-economic phenomenon that requires its own approach. When studying it, it is appropriate to study, take into account, and rely on the general laws and principles of employment. It has an impact on the level of employment of the population, especially women. According to scientists, "the lack of a clear attitude towards work among all women, the lack of highly qualified female professionals, the increasing leadership role of women in running the family economy, and the persistence of stereotypes regarding women's socially useful work, are factors in social perceptions of this issue." "The existence of gender differences is reflected in the low level of professional and leadership aspirations of rural women today." Social and economic mechanisms are the main means of providing the population with work, increasing the need for labor and supporting the effective supply of labor. The study of these relationships at the macro level is considered the main tool for regulating the labor market, in which social and economic mechanisms play a special role in increasing the demand for female labor and helping to support and strengthen its supply.